RESULTS OF EXPLORATORY PURSE SEINING BETWEEN COCHIN AND GOA - Shanmugavelu, C R; Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
Of the nine fishing squares covered along thÂ« Cochin-Goa coast by the purse seiners operated by the Integrated Fisheries Project, Cochin, and the Explorstory Fisheries Project at Mangalore and Goa during the period, January 1975 to June 1978, the ansas 6-76, 10-76 and l’5-73, between the latitude 9Â°10’-15Â°40’’N and longitude 73Â°30’-76Â°30’E, were explored intensively. Out of the total of 10,81,951 kg of fishes landed as a result, 72% of the catch comprisied of oil sardine